The post-war dream a novel - Cullin, Mitch (Nan A. Talese/Doubleday, 2008)
Living in a gated community outside of Tucson, Hollis and Debra, a couple in their golden years, are forced to confront the trauma of the past when Debra, diagnosed with cancer, asks her husband to relive his memories of the Korean War.
Keywords: Older men / Fiction; Korean War, 1950-1953 / Veterans / Fiction; Korean War, 1950-1953 -- Veterans -- Fiction; Older men -- Fiction; Psychological fiction